How do you solve #y'+3y=0# given y(0)=4?

Answer 1

# y = 4e^(-3x) #

We have # y'+3y=0 #, or:
# dy/dx + 3y = 0 #

This is a first order linear ordinary differential equation and so we can derive an Integrating Factor using:

IF # = e^(int 3dx) # # \ \ \ = e^(3x) #

So multiplying the DE by the IF gives:

# e^(3x)dy/dx + 3ye^(3x) = 0 #

Thanks to the product rule this can now be written as the derivative of a single product:

# d/dx(ye^(3x)) = 0 #

Which can now easily be solved to give;

# ye^(3x) = A # # :. y = Ae^(-3x) #
We know that #y(0)=4 => Ae^0=4 => A=4 #
Hence, the solution is: # y = 4e^(-3x) #
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

#y=4e^(-3x)#

We have the separable differential equation:

#y'+3y=0#

Which can be rearranged as:

#dy/dx+3y=0#
#dy/dx=-3y#
Rearranging this by separating the variables, that is, treating #dy/dx# as division and getting the #y# terms on one side and the #x# terms on the other, we see that:
#dy/y=-3dx#

Integrate both sides:

#intdy/y=-3intdx#
#lnabsy=-3x+C#
Use the initial condition #y(0)=4# to solve for #C#:
#lnabs4=-3(0)+C#
#C=ln(4)#

Then:

#lnabsy=-3x+ln(4)#
Solving for #y#:
#absy=e^(-3x+ln(4))#

Rewriting using exponent rules:

#absy=e^(-3x)e^ln(4)#
#absy=4e^(-3x)#
#4e^(-3x)# is positive for all real values of #x#, so the absolute value bars are not necessary.
#y=4e^(-3x)#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 3

To solve the differential equation ( y' + 3y = 0 ) with the initial condition ( y(0) = 4 ), you can use the method of separation of variables.

  1. Rewrite the equation in the form ( y' = -3y ).
  2. Separate variables by dividing both sides by ( y ) and multiplying both sides by ( dx ): ( \frac{dy}{y} = -3dx ).
  3. Integrate both sides:
    • Integrate ( \frac{dy}{y} ) to get ( \ln|y| ).
    • Integrate ( -3dx ) to get ( -3x + C ), where ( C ) is the constant of integration.
  4. Combine the results: ( \ln|y| = -3x + C ).
  5. Solve for ( y ) by exponentiating both sides: ( |y| = e^{-3x + C} ).
  6. Apply the initial condition ( y(0) = 4 ):
    • When ( x = 0 ), ( |y| = e^C ).
    • Since ( |y| = 4 ), ( e^C = 4 ).
    • Therefore, ( C = \ln(4) ).
  7. Substitute ( C = \ln(4) ) back into the equation: ( |y| = e^{-3x + \ln(4)} ).
  8. Simplify and solve for ( y ):
    • ( |y| = e^{\ln(4) - 3x} = 4e^{-3x} ).
    • ( y = \pm 4e^{-3x} ).
  9. Apply the initial condition to find the particular solution:
    • ( y(0) = 4 ) implies ( y = 4e^0 = 4 ).
  10. Hence, the solution to the initial value problem is ( y = 4e^{-3x} ).
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7